5.设 f(x,y)=x+(y-1)arcsinxy, 求fx(x,1),f,(0 ,1).(15分)
1个回答
关注
展开全部
您好,要计算 f 的偏导数 fx(x, 1) 和 fy(0, 1),可以使用偏导数的定义。
首先,计算 fx(x, 1):
fx(x, y) = 1 + (y - 1) * (d(arcsin(xy)) / dx)
= 1 + (y - 1) * (1 / √(1 - (xy)^2)) * (d(xy) / dx)
= 1 + (y - 1) * (1 / √(1 - (xy)^2)) * y
= 1 + (y^2 - y) / √(1 - (xy)^2)
将 y 替换为 1:
fx(x, 1) = 1 + (1^2 - 1) / √(1 - (x*1)^2)
= 1
接下来,计算 fy(0, 1):
fy(x, y) = (d(x) / dy) + (y - 1) * (d(arcsin(xy)) / dy)
= 0 + (y - 1) * (1 / √(1 - (xy)^2)) * (d(xy) / dy)
= (y - 1) * (1 / √(1 - (xy)^2)) * x
咨询记录 · 回答于2024-01-15
5.设 f(x,y)=x+(y-1)arcsinxy, 求fx(x,1),f,(0 ,1).(15分)
您好,要计算 f 的偏导数 fx(x, 1) 和 fy(0, 1),可以使用偏导数的定义。
首先,计算 fx(x, 1):
fx(x, y) = 1 + (y - 1) * (d(arcsin(xy)) / dx)
= 1 + (y - 1) * (1 / √(1 - (xy)^2)) * (d(xy) / dx)
= 1 + (y - 1) * (1 / √(1 - (xy)^2)) * y
= 1 + (y^2 - y) / √(1 - (xy)^2)
将 y 替换为 1:
fx(x, 1) = 1 + (1^2 - 1) / √(1 - (x*1)^2)
= 1
接下来,计算 fy(0, 1):
fy(x, y) = (d(x) / dy) + (y - 1) * (d(arcsin(xy)) / dy)
= 0 + (y - 1) * (1 / √(1 - (xy)^2)) * (d(xy) / dy)
= (y - 1) * (1 / √(1 - (xy)^2)) * x
将 x 替换为 0,y 替换为 1:fy(0, 1) = (1 - 1) * (1 / √(1 - (0*1)^2)) * 0= 0所以,fx(x, 1) = 1,fy(0, 1) = 0。